Linking Empowering Leadership and Employee Work Engagement: The Effects of Person-Job Fit, Person-Group Fit, and Proactive Personality - Cai, Di; Cai, Yahua; Sun, Yan; Ma, Jinpeng (Frontiers in Psychology, 2018)
Based on person-environment fit theory, this study examined the effects of empowering leadership on employee work engagement. We also investigated the mediating mechanism of person-job fit and person-group fit. In addition, we explored employee proactive personality’s moderating role between empowering leadership and the above two kinds of fit, and then the set of indirect effects. Using a survey sample of 6179 employees from a technology company in China, we found that empowering leadership has a positively indirect influence on employees work engagement though person-job fit and person-group fit. Further, moderated mediation analysis revealed proactive personality augmented empowering leadership direct effect on person-job fit and person-group fit and indirect effect on work engagement. Theoretical and practical implications were also discussed.